Fine-tuning terminal solvent ligands to rationally enhance the energy barrier in dinuclear dysprosium single-molecule magnets. Issue 1 (2nd December 2016) - Zhang, Kun; Yuan, Chen; Guo, Fu-Sheng; Zhang, Yi-Quan; Wang, Yao-Yu
Abstract : By replacing hydrogen atoms with electron-donating group on terminal solvent ligands, we were able to create a three-fold enhancement of the energy barrier in two dinuclear dysprosium single-molecule magnets. Abstract : In search of simple approaches to rationally enhance the energy barriers in polynuclear dysprosium single-molecule magnets, a new system containing two structurally closely related dinuclear dysprosium complexes, namely [Dy2 (L)2 (DBM)2 (DMF)2 ] (1 ) and [Dy2 (L)2 (DBM)2 (DMA)2 ]·2DMA (2 ) (HDBM = dibenzoylmethane, H2 L = 2-hydroxy- N ′-(2-hydroxy-3-methoxybenzylidene)benzohydrazide), is introduced and the structure-dependent magnetic properties are investigated. The two complexes display only slight variations in the coordination geometries of the Dy(iii ) ion but display remarkably different magnetic behaviors. By replacing the DMF (dimethylformamide) ligand in complex1 with DMA (dimethylacetamide) in2 while retaining the same coordination atoms, we were able to create a 3-fold enhancement in the energy barrier, from 24 K for complex1 to 77 K for complex2 . Complete-active-space self-consistent field (CASSCF) calculations revealed that the charge distribution surrounding the Dy(iii ) centers in1 and2 is the key factor in determining the relaxation properties of the SMMs. The introduction of an electron-donating CH3 group in DMA to replace the hydrogen in DMF resulted in a larger average charge along the magnetic axes of complex2 compared to complex1, which resulted in a stronger easy-axis ligand field, thus increasing the energy difference between the ground and the first excited states of complex2 . This work presents a simple method to rationally enhance the energy barrier in polynuclear lanthanide SMMs through fine-tuning of the electrostatic potential of the atoms along the magnetic axis.